The Emerging Role of the Cannabinoid Receptor Family in Peripheral and Neuro-immune Interactions - Haugh, Orla; Penman, June; J. Irving, Andrew; A. Campbell, Veronica (Current Drug Targets, 2016)
The classical endogenous cannabinoid (CB) system is composed of the endocannabinoid signalling molecules, 2-arachidonoyl glycerol (2-AG) and anandamide (AEA) and their G-protein coupled receptors (GPCR), CB1 and CB2 which together constitutes the endocannabinoid system (ECS). However, putative, novel lipid-sensing CB receptors have recently been identified, including the orphan GPR55 and GPR18 receptors that are regulated by cannabinoid-like molecules and interact with CB system. CB receptors and associated orphan GPCRs are expressed at high levels in the immune and/or central nervous systems (CNS) and regulate a number of neurophysiological processes, including key events involved in neuroinflammation. As such, these receptors have been identified as emerging therapeutic targets for a number of brain disorders in which neuroinflammation is a key feature, including multiple sclerosis (MS) and Alzheimer’s disease (AD). This review will consider the role of the wider cannabinoid receptor superfamily in mediating immune function with a focus on the immune processes that contribute to neuroinflammatory conditions.
Keywords: Cannabinoid